USO DE PLANTAS DE COBERTURA E SUA INFLUÊNCIA NA DESCOMPACTAÇÃO DO SOLO - SILVA, Fagner Luiz Rodrigues; GUIMARÃES JUNNYOR, Wellingthon da Silva; RODRIGUES, Gustavo Sanches; SANTOS, Maria Aparecida Do Nascimento; MARTINS, Murilo Battistuzzi (ANAIS DO ENIC, 2024)
-